Agricultural R&D in the Philippines: Policy, investments, and institutional profile - Stads, Gert-Jan; Faylon, Patricio S.; Buendia, Leah J. (International Food Policy Research Institute, 2007)
This report presents an overview of the Philippine national agricultural R&D system in the context of the country’s wider national science and technology (S&T) policy. The discussion includes institutional developments and recent trends in human and financial resources based on data collected under the Agricultural Science and Technology Indicators (ASTI) initiative. With a total of close to 4,000 full-time equivalent researchers in 2002, the Philippines has one of the largest agricultural research systems in Asia. But in terms of total agricultural research spending, the Philippines ranks behind more economically advanced Asian countries such as Malaysia and South Korea. Nonetheless, agricultural R&D spending in the Philippines has shown significant growth in recent years. In 2002, the country invested $269 million in agricultural R&D (in 2000 international dollars), which is an increase of two-thirds over the level recorded a decade earlier. Public agricultural R&D in the Philippines is heavily reliant on government sources of support. In 2002, the Philippine government provided more than 85 percent of funding to the government agencies. In recent years, however, the share of internally generated resources has gradually increased. Foreign donor support plays only a marginal role in the Philippine agricultural R&D system, distinguishing it from some other countries in the region. The organization of public agricultural R&D in the Philippines is complex. The Philippine Council for Agriculture, Forestry and Natural Resources Research and Development (PCARRD) acts as the central coordinating body providing support to 132 implementing R&D agencies collectively called the National Agriculture and Resources Research and Development Network (NARRDN) as well as 14 region-based consortia. Compared to most countries in the Asia-Pacific region, the private sector plays a relatively important role in conducting agricultural R&D in the Philippines. We estimated that about 18 percent of total (public and private) spending in agricultural R&D was done by the private sector, mostly fruit plantations.